Opportunities for Finnish Wellness Tourism in Petrozavodsk, Russia. Case: Karelia & SPA and Onego Palace. - Katkeviciute, Violeta (Karelia-ammattikorkeakoulu (Pohjois-Karjalan ammattikorkeakoulu), 2016)
Currently, the popularization of healthier lifestyles in Western societies encourages people to combine travelling, health promotion and well-being. In such a circumstance, wellness tourism has become more popular and has provided market opportunities for companies working in the wellness industry to find niches in the market. The purpose of the research is to find out if there is a potential consumer female market in Finland, particularly in Joensuu, for Russian (Petrozavodsk) companies working in the wellness industry. Collecting key information was performed by using traditional printed and internet sources, a survey and interviews of specialists working in the wellness industry in Joensuu, and a field study in Petrozavodsk. The research emphasized price, because it is the most important factor in the decision-making process of the target group. The project proved that there is a substantial potential consumer market in Finland for Russian companies working in the wellness industry. Petrozavodsk's companies have a good opportunity to successfully operate in the market because of lower prices on services, strong quality and a variety of cosmetic services under certain circumstances (developing a system of spa packages and expansion of the ranges of spa procedures).